STUDENT ENGAGEMENT AT THE HIGHER LEARNING INSTITUTIONS: The Case of Malaysia and the United Arab Emirates - Nurahimah Mohd Yusoff (Aceh International Journal of Social Science, 2012)
Abstract - Universities in Malaysia and the United Arab Emirates (UAE), just like other Higher Education Institutions (HEIs), strive to be at the forefront of academic excellence. Towards this end, HEIs endeavour to provide their students, their primary clientele with the most conducive learning environment in order to maximise their potentials and prepare them to the real world of work. Do the students really make the most of the learning experiences in the university? Are the students really actively “engaged” in the teaching programmes and learning activities provided by the university? What might be the implications of student engagement to curriculum, instruction, policy and decision making, and educational administration? This paper focused on the level of academic challenge provided to students. In this study, “academic challenge” was based on study time and course requirements for reading, writing, and application of higher-order thinking skills rather than on student judgments of the difficulty of the coursework (Carini and Kuh, 2003). Specifically, this investigation attempted to ascertain the types of engagement activities at the HEIs of Malaysia and the UAE. Interesting findings are presented, and recommendations are offered in light of student engagement in the context of higher education.